High-Resolution Comparative Genomics of Salmonella Kentucky Aids Source Tracing and Detection of ST198 and ST152 Lineage-Specific Mutations - Soltys, Rachel C.; Sakomoto, Carson K.; Oltean, Hanna N.; Guard, Jean; Haley, Bradd J.; Shah, Devendra H. (Frontiers in Sustainable Food Systems, 2021)
Non-typhoidal Salmonella (NTS) is a major cause of foodborne illness globally. Salmonella Kentucky is a polyphyletic NTS serovar comprised of two predominant multilocus sequence types (STs): ST152 and ST198. Epidemiological studies have revealed that ST152 is most prevalent in US poultry whereas ST198 is more prevalent in international poultry. Interestingly, ST152 is sporadically associated with human illness, whereas ST198 is more commonly associated with human disease. The goal of this study was to develop a better understanding of the epidemiology of ST198 and ST152 in WA State. We compared the antimicrobial resistance phenotypes and genetic relationship, using pulsed-field gel electrophoresis, of 26 clinical strains of S. Kentucky isolated in Washington State between 2004 and 2014, and 140 poultry-associated strains of S. Kentucky mostly recovered from the northwestern USA between 2004 and 2014. We also sequenced whole genomes of representative human clinical and poultry isolates from the northwestern USA. Genome sequences of these isolates were compared with a global database of S. Kentucky genomes representing 400 ST198 and 50 ST152 strains. The results of the phenotypic, genotypic, and case report data on food consumption and travel show that human infections caused by fluoroquinolone-resistant (FluR) S. Kentucky ST198 in WA State originated from outside of North America. In contrast, fluoroquinolone-susceptible (FluS) S. Kentucky ST198 and S. Kentucky ST152 infection have a likely domestic origin, with domestic cattle and poultry being the potential sources. We also identified lineage-specific non-synonymous single nucleotide polymorphisms (SNPs) that distinguish ST198 and ST152. These SNPs may provide good targets for further investigations on lineage-specific traits such as variation in virulence, metabolic adaptation to different environments, and potential for the development of intervention strategies to improve the safety of food.